2016
DOI: 10.3347/kjp.2016.54.1.97
|View full text |Cite
|
Sign up to set email alerts
|

Serological Detection of <i>Borrelia burgdorferi</i> among Horses in Korea

Abstract: Lyme disease is a tick-borne zoonotic infectious disease caused by Borrelia burgdorferi. The present study assessed the infection status of B. burgdorferi among horses reared in Korea using ELISA and PCR. Between 2009 and 2013, blood samples were collected from 727 horses throughout Korea. Data for each animal including age, gender, breed, and region of sample collection were used for epidemiological analysis. Overall, 38 (5.2%; true prevalence: 5.5%) of 727 horses were seropositive by ELISA. There were statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 26 publications
2
22
0
Order By: Relevance
“…13,19,32 Moreover, the serological prevalence of Lyme disease in horses and dogs has also been reported. 33,34 However, information detailing the prevalence of Borrelia spp. in animals is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…13,19,32 Moreover, the serological prevalence of Lyme disease in horses and dogs has also been reported. 33,34 However, information detailing the prevalence of Borrelia spp. in animals is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…It has been indicated that the majority of horses that were positive on initial testing did not have a different test result 5-17 months later (Funk et al, 2016). Recently, Lee et al (2016) showed statistically significant differences according to breed and region where variances might be attributed to the ecology of vector ticks and climate conditions.…”
Section: Epidemiologymentioning
confidence: 99%
“…The seroprevalence of Lyme borreliosis in horses varies with geographical areas. In some areas of the north-eastern USA it is about 33-50% (Funk et al, 2016;Magnarelli et al, 2000), 9.8-42.8% in Brazil (Basile et al, 2016), 31-48% in France (Maurizi et al, 2010), 29% in Denmark (Hansen et al, 2010), 26% in Poland (Stefanciková et al, 2008), 24% in Italy (Ebani et al, 2012), 6% in Turkey (Bhide et al, 2008), and 5.5% in Korea (Lee et al, 2016). Older horses are more prone for positive test response than younger ones (Ebani et al, 2012;Funk et al, 2016).…”
Section: Epidemiologymentioning
confidence: 99%
“…In 2016, Lee et al [ 8 ] conducted a study of B. burgdorferi seroprevalence between 2009 and 2013 in domestic horse sera. Among a total of 727 horses studied, 5.5% showed antibody prevalence, with meaningful variation across regions ( p < 0.001).…”
mentioning
confidence: 99%
“…Second, workers in the horse industry, such as horse keepers, trainers, and jockeys, should be regarded as a high-risk group. Third, Jeju is likely to see more LB cases in the future due to climate change [ 8 ].…”
mentioning
confidence: 99%